The Sciences’ Media Connection –Public Communication and its Repercussions
XII, 380 p.
Keywords: The Yearbook addresses the overriding question: what are the effects of the ‘opening up’ of science to the media? Includes theoretical considerations and a host of empirical studies covering different configurations providing an in-depth analysis of the sciences’ media connection and its repercussions on science itself. They help to form a sound judgement on this recent development.